Wawasan Al-Qur’an tentang Kode Etik Jurnalisme - Mugni, Abdul (Pascasarjana IAIN Lhokseumawe, 2019)
Media as a channel to influence the audience has a lot to contribute to the formation of public opinion, including the role fostering harmony among religious believers (as in the case of Papua Tolikara). Media always deal with the business of words to create a public discourse. Discourse producing ideas or concepts are believed to be true, the news industry that produces information openly and can be used by readers authentic documents. Communication will crush if we allow media becomes sightless instrument for market behalf, economy and technology. No until we just clever pack news to establish also constitute news representation with manner, just thus media can answer longing and the need most deep readers, audience or beholder. The role of media is very important in the events, in addition to constructing the main bustle world of social reality, also the message of the media is very likely significantly affect the attitude of religious communities such as in Indonesia. Therefore, horizontal conflict in Papua is an exciting event to be carefully considered, especially analyzing the content of the news published media. Journalistic dedication stake in the defence of human values that put the principles of Journalistic Code of Ethics or Code of Journalists of Indonesias, fairness doctrine, cover both sides or news balance and check and recheck in coverage as a key principle.